Comparison of the Prophylactic Effect of Ondansetron and Dexamethasone on Postoperative Nausea and Vomiting after Intrathecal Meperidine in Women Scheduled for Elective Cesarean Section - N Banihashem (Babol University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVE: Intrathecal meperidine is highly effective to enhance postoperative analgesia in women undergoing cesarean delivery. However, spinal meperidine is associated with a frequent incidence of nausea, vomiting and pruritus which can limit its use. The objective of this study was to compare the prophylactic effect of ondansetron and dexamethasone in preventing postoperative nausea and vomiting (PONV) during intrathecal injection of meperidine in women undergoing elective cesarean section.METHODS: In a randomized double blind clinical trial 50 women were scheduled for elective cesarean section. They were randomly allocated to dexamethasone (n=25) or ondansetron (n=25) groups. The patients were under spinal anesthesia with 50mg lidocaine and 25mg meperidine. They received 8 mg dexamethasone or 8 mg ondansetron intravenously just before surgery. The patients were evaluated for PONV and pruritus during surgery, recovery period, 6, 12 and 24h after surgery.FINDINGS: There were not significant differences in patients characteristics, hemodynamic variables, and sensory level of anesthesia. Nausea was observed in 4 (16%) and 7 (28%) of women in dexamethasone and ondansetron groups, respectively (p=0.496). Vomiting was observed in 3 (12%) and 4 (16%) of women in ondansetron and dexamethasone groups, respectively (p=1). No nausea and vomiting were observed 2 hours after spinal anesthesia. The incidence of pruritus was observed in 6 (24%) and 7 (28%) of women in dexamethasone and ondansetron groups, respectively. CONCLUSION: The results of this study showed that ondansetron is as effective as dexamethasone for preventing nausea, vomiting and pruritus after intrathecal injection of meperidine in women undergoing elective cesarean section. So intravenous dexamethasone is a good choice for preventing nausea and vomiting after intrathecal injection of meperidine.